2015
DOI: 10.1515/acgeo-2015-0001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the North Atlantic Oscillation on the Thermal Characteristics of Lakes in Poland

Abstract: A b s t r a c tThis paper presents the effect of the North Atlantic Oscillation (NAO) on the thermal characteristics of lakes in Poland. In the analysis, the use was made of monthly air temperatures recorded at fifteen meteorological stations, water temperatures of twelve lakes, and Hurrell's winter NAO indices. Over the study period , there was a marked increase in the temperatures of both, air and lake waters. Depending on the NAO phase, water temperatures were observed to depart from mean values, being mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 22 publications
2
22
0
Order By: Relevance
“…This increase at the Poznań station is consistent with the course of air temperature in other regions of Poland, and it is directly reflected in the elevation of lake water temperatures [40]. Such a situation affects changes in the components of the water balance of the lakes.…”
Section: Discussionsupporting
confidence: 77%
“…This increase at the Poznań station is consistent with the course of air temperature in other regions of Poland, and it is directly reflected in the elevation of lake water temperatures [40]. Such a situation affects changes in the components of the water balance of the lakes.…”
Section: Discussionsupporting
confidence: 77%
“…The analysis of approximately a dozen lakes in Poland in the years 1961-2010 showed that warming of the surface water layers in lakes is particularly evident in spring (April, May) and summer months (July, August), where e.g. in the case of Lake Lubie, in May an increase by 1.02°C per decade was recorded [14]. A similar situation was observed in the case of lakes analysed in Estonia [15].…”
Section: Resultssupporting
confidence: 53%
“…In the monthly cycle, the highest temperature increase was determined for July (0.73°C·dec -1 ) and April (0.73°C·dec -1 ). Due to strong correlations of temperature of air and water [22], an increase in the former will contribute to an increase in the latter. As a consequence, heat resources accumulated in lakes increase [23].…”
Section: Resultsmentioning
confidence: 99%